Online Books at Columbia Measurement and Early Results on Use, Satisfaction, and Effect - Mandel, Carol A.; Summerfield, Mary C.; Kantor, Paul ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
The Online Books Evaluation Project at Columbia University (New York) explores the potential for online books to become significant resources in academic libraries. The Project confronts and explores a set of feasibility issues, including publishers' ability to provide books of various types and vintages in forms conducive to conversion to online formats and the ability to convert them to online books that will serve users' needs and preferences. This paper focuses on the first of the Project's elements, user response, and reports on: (1) the conceptual framework of the Project; (2) background information on the status of the collection and other relevant Project elements, particularly design considerations; (3) methodology for measuring adoption of online books by the Columbia community; (4) current findings on relevant environmental factors, including access to online resources; (5) current findings on use of online books and other online resources; and (6) current findings on attitudes toward online books. This paper also reflects the experiences of the Project as a case study, specifically, the problems encountered evaluating online resources and problems encountered in producing online books. Fifty-nine tables present statistics. (Contains 47 references.) (AEF)
Availability: Association of Research Libraries (ARL) Web site: http://www.arl.org/scomm/scat/.
ERIC Note: Paper presented at the Conference on Scholarly Communication and Technology (Atlanta, GA, April 24-25, 1997); see IR 056 774.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Libraries; Access to Computers; Access to Information; Books; Case Studies; Electronic Libraries; Electronic Publishing; Evaluation Methods; Higher Education; Information Sources; Information Technology; Library Materials; Online Systems; Publishing Industry; Reading Materials; Tables (Data); User Needs (Information); Columbia University NY -- Electronic Resources; Reports, Descriptive; Speeches/Meeting Papers